Consensus guidelines on managing Rett syndrome across the lifespan. Issue 1 (13th September 2020) - Fu, Cary; Armstrong, Dallas; Marsh, Eric; Lieberman, David; Motil, Kathleen; Witt, Rochelle; Standridge, Shannon; Nues, Paige; Lane, Jane; Dinkel, Tristen; Coenraads, Monica; von Hehn, Jana; et al.
Abstract : Background: Rett syndrome (RTT) is a severe neurodevelopmental disorder with complex medical comorbidities extending beyond the nervous system requiring the attention of health professionals. There is no peer-reviewed, consensus-based therapeutic guidance to care in RTT. The objective was to provide consensus on guidance of best practice for addressing these concerns. Methods: Informed by the literature and using a modified Delphi approach, a consensus process was used to develop guidance for care in RTT by health professionals. Results: Typical RTT presents early in childhood in a clinically recognisable fashion. Multisystem comorbidities evolve throughout the lifespan requiring coordination of care between primary care and often multiple subspecialty providers. To assist health professionals and families in seeking best practice, a checklist and detailed references for guidance were developed by consensus. Conclusions: The overall multisystem issues of RTT require primary care providers and other health professionals to manage complex medical comorbidities within the context of the whole individual and family. Given the median life expectancy well into the sixth decade, guidance is provided to health professionals to achieve current best possible outcomes for these special-needs individuals.